Pluralisme Hukum dalam Pengelola ANALISIS HISTORIS DAN YURIDIS TERHADAP PENGELOLAAN WAKAF LAHAN DI KESULTANAN SAMBAS KALIMANTAN BARAT - Vinna Lusiana (Al-Amwal : Journal of Islamic Economic Law, 2025)
Abstract Purpose – This study addresses the Legal-Functional Paradox in land waqf management within the Sambas Sultanate, West Kalimantan. Over 78% of historical waqf assets face legal vulnerability due to the fundamental discrepancy between the living law (oral/customary waqf) and the formal state law (Law No. 41/2004). The research aims to (1) describe empirical waqf practices; (2) analyze structural constraints (legal dualism, geographic challenges, and Nadzir's cultural-managerial resistance); and (3) formulate the sustainable and integrative Sambas Sultanate Land Waqf Management Model (MPWK-KS). Method – Utilizing a Juridical-Empirical approach, this qualitative research deconstructs the existing legal gap and legal pluralism. Data were collected via purposive sampling from 12 key informants (Sultan/representative, hybrid Nadzir, BWI/BPN officials) through in-depth interviews, participatory observation, and archive documentation. Analysis employed the Miles & Huberman interactive analysis, critically synchronizing field findings with Maqāṣid al-Sharī‘ah principles, particularly Hifẓ al-Māl (preservation of wealth). Result – Key findings indicate that the primary constraints are the deep cultural-juridical resistance of the Nadzir (91% untrained in PSAK 112 compliance) and a highly inefficient BPN certification process (minimum 102 days) due to bureaucracy and geographic barriers. MPWK-KS is formulated as a hybrid governance framework that integrates the Sultan's spiritual authority with the BWI Nadzir's professional capability. The central novelty is the Fast Track Legalization pillar, recognizing the Sultanate’s Decree as a Novum Hukum (New Legal Basis) for pre-certification, thus enabling productive waqf development. Implication – As a practical implication, MPWK-KS must be operationalized through a Joint Regulation (Perber) between the Sambas Sultanate, BWI, and the Ministry of ATR/BPN. This Model serves as a vital national prototype for the reconciliation of laws within the context of Legal Pluralism, transforming non-formal waqf assets into legal, accountable social capital that comprehensively strengthens the Islamic identity of the Sambas Malay community.